The Central & Provincial Relationship in the Context of 18th Amendment: (A Case Study of Punjab Province) - Dr. Saeed Ahmad; Muhammad Faisal Nadeem Bhatti; Farhat Naz Qureshi; Siddique Ahmad (Al-Qanṭara, 2023)
Federalism was introduced to regulate and manage the relationship between Federal & Central Units. It is a tool for harmonizing a sense of independence without destroying National Unity. State affairs are regulated by the central government, and regional interests are regulated by the state governments. According to Dicey, “a political instrument aimed at reconciling national unity and defending the rights of the state.” This provision is regulated by the Constitution. The emergence of connections is the result of afferent and efferent tendencies. Combining troops into a confederation carries common risks and economic benefits. This is how the United States, Switzerland and Australia emerged. The second is the geographical expansion of the country, leading to Decentralization & Federalization. In 2010 18th Amendment had a positive effect on the development of the Constitution. The positive effect happens with the first interesting effect with Centre Province issue. The 18th Amendment strengthens the Provincial Autonomy the list of laws has been deleted due to the amendment of Section 142 of Constitution. These Subjects were transferred to the Provinces. Still the President have authority to appoint the Governors but the governor must be on the electoral roll and live in a respected area. The Federal Govt. would consult with the state government before in various issues. And that effectively handles differences between states and centers. In Section 160, NFC must be assigned at least the previous.